2020
DOI: 10.1038/s41598-020-69736-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term administration of recombinant canstatin prevents adverse cardiac remodeling after myocardial infarction

Abstract: Myocardial infarction (Mi) still remains a leading cause of mortality throughout the world. An adverse cardiac remodeling, such as hypertrophy and fibrosis, in non-infarcted area leads to uncompensated heart failure with cardiac dysfunction. We previously demonstrated that canstatin, a c-terminus fragment of type IV collagen α2 chain, exerted anti-remodeling effect against isoproterenolinduced cardiac hypertrophy model rats. In the present study, we examined whether a long-term administration of recombinant ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…We previously reported that the long-term administration of canstatin (20 µg/kg/day, 28 days, i.p.) had no effect on cardiac function in normal rats [15,30]. In addition, we recently demonstrated that the administration of canstatin (20 µg/kg/day, 28 days, i.p.)…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We previously reported that the long-term administration of canstatin (20 µg/kg/day, 28 days, i.p.) had no effect on cardiac function in normal rats [15,30]. In addition, we recently demonstrated that the administration of canstatin (20 µg/kg/day, 28 days, i.p.)…”
Section: Discussionmentioning
confidence: 91%
“…In addition, we recently demonstrated that the administration of canstatin (20 µg/kg/day, 28 days, i.p.) improved survival rate and cardiac dysfunction in MI model rats [30]. Thus, it is suggested that canstatin might exert an anti-arrhythmic effect without exaggerating cardiac dysfunction after MI.…”
Section: Discussionmentioning
confidence: 94%
“…In veterinary studies, various anesthetic combinations have been previously proven to be effective to induce MI models in rodents such as ketamine and xylazine ( 9 , 10 ), a mixture of ketamine, xylazine and acepromazine ( 11 ), sodium pentobarbital ( 12 ), chloral hydrate 10% ( 13 , 14 ) and inhalational anesthesia as isoflurane (induction: 5%, maintenance: 2.5%) with buprenorphine was subcutaneously administered for analgesia ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%